Non-Linear Dynamics of Yield Spreads and Inflation: Evidence from India - Gupta, Mayank; Pawar, Amit; Seet, Subrat Kumar; Suraj, S. (Journal of Quantitative Economics, 2024)
Inflation expectations hold utmost importance in central bank policymaking as they serve as a critical determinant of economic stability and the effectiveness of monetary policy measures. Based on this motivation, this study empirically examines the infor
Keywords: Central Bank Policymaking; Term Structure; Threshold Models; Yield Spreads; Inflation Expectations